Optimization of machine tools by using the maximum productivity rate - A. M., Ahmed Alwaise; Usubamatov, Ryspek, Prof. Dr.; Saifulddin, Abdul Manan, Dr.; Bhuvenesh, Rajamony, Assoc. Prof. Dr. (INSInet Publication, 2012)
Link to publisher's homepage at http://www.insipub.com/index